Curricular programs and philosophies in public administration a regional perspective - Cardenas, Benito C. (Philippine Journal of Public Administration, 1990)
A lot remains to be planned and done to effectively achieve Public Administration education program goals in the Ilocos Region and Cordillera Administrative Region. To prospective Masters of Public Administration (MPA) students, what may be of paramount importance are matters of curriculum, faculty expertise, tuition, and financial aid; to the prospective MPA faculty, questions of faculty reputation, teaching loads, research opportunities, salary, cost of living, and desirability of location may be of greater importance; and to the prospective employer, those involving program strengths, program emphasis, and general reputation may be more weighty. Also discussed are issues on the quality of MPA students, attraction and retention of quality faculty, moral and financial support from the academic administration, relevance, professionalism and professional ethics in public administration, and low graduation rates. Finally, eight recommendations are offered for consideration by the Association of Schools of Public Administration in the Philippines, Inc. in assisting its member institutions in appropriate collaborative undertakings.